Cobalt Single Atom Incorporated in Ruthenium Oxide Sphere: A Robust Bifunctional Electrocatalyst for HER and OER. Issue 4 (9th December 2021) - Shah, Khadim; Dai, Ruoyun; Mateen, Muhammad; Hassan, Zubair; Zhuang, Zewen; Liu, Chuhao; Israr, Muhammad; Cheong, Weng‐Chon; Hu, Botao; Tu, Renyong; Zhang, Chao; Chen, Xin; et al.
Abstract: The development of highly active and stable bifunctional noble‐metal‐based electrocatalysts for the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) is a crucial goal for clean and renewable energy, which still remains challenging. Herein, we report an efficient and stable catalyst comprising a Co single atom incorporated in an RuO2 sphere for HER and OER, in which the Co single atom in the RuO2 sphere was confirmed by XAS, AC‐STEM, and DFT. This tailoring strategy uses a Co single atom to modify the electronic structures of the surrounding Ru atoms and thereby remarkably elevates the electrocatalytic activities. The catalyst requires ultralow overpotentials, 45 mV for HER and 200 mV for OER, to deliver a current density of 10 mA cm −2 . The theoretical calculations reveal that the energy barriers for HER and OER are lowered after incorporation of a cobalt single atom. Abstract : A Co single atom is incorporated in a RuO2 sphere through a one‐pot hydrothermal process, as revealed by EXAFS, HRTEM, and AC‐STEM. The Co single atoms could tailor the local electronic structure of the bifunctional electrocatalyst for high‐performance HER and OER, which significantly reduces the energy barrier, and the catalyst shows the lowest overpotential of 45 mV for HER and 200 mV for OER at a current density of 10 mA cm −2 .